Extra criterial antiphospholipid antibodies in patients with antiphospholipid syndrome and systemic lupus erythematosus (preliminary data) - F. A. Cheldieva; T. M. Reshetnyak; M. V. Cherkasova; A. M. Lila (Современная ревматология)
The role of antiphospholipid antibodies (aPL), which are not included in the classification criteria, in antiphospholipid syndrome (APS) andsystemic lupus erythematosus (SLE) is not well understood.Objective: to determine the frequency of detection of IgG antibodies to domain 1 of β2-glycoprotein 1 (IgG-aβ2GP1-D1), IgA antibodiesto cardiolipin (aCL) and IgA antibodies to β2-glycoprotein 1 (IgA-a β2GP1) in patients with primary APS and APS in combination withSLE.Patients and methods. The study included 63 patients in whom IgG/IgM-aCL and IgG/IgM-aβ2GP1 were detected by enzyme-linkedimmunosorbent assay (ELISA) and IgG/IgM/IgA-aCL, IgG/IgM/IgA-aβ2GP1 and IgG-aβ2GP1-D1 by chemiluminescence analysis (CLA).Results and discussion. The detection rate of IgG-aβ2GP1-D1 was 76%, IgA-aCL – 56%, IgA-aβ2GP1 – 48%. Isolated positivity for IgA-aCL,IgA-aβ2GP1, IgG-aβ2GP1-D1 was not observed. The presence of IgA-aCL, IgA-aβ2GP1, IgG-aβ2GP1-D1 was associated with high positivity forIgG/IgM-aCL and IgG/IgM-aβ2GP1. There was a statistically significant relationship between IgA-aCL/IgA-aβ2GP1 and the standard aPLprofile, as well as IgG-aβ2GP1-D1, IgG-aCL and IgG-aβ2GP1.Conclusion. A high detection rate of IgG-aβ2GP1-D1, IgA-aCL, IgA-aβ2GP1 was found in patients with APS. A statistically significant relationshipwas found between IgA-aCL/IgA-aβ2GP1 and the standard aPL profile, as well as IgG-aβ2GP1-D1 with IgG-aCL and IgG-aβ2GP1.